Biological properties of essential oils: an updated review - Adorjan, Barbara; Buchbauer, Gerhard (Flavour and fragrance journal, 2010)
In the last few years more and more studies on the biological properties of essential oils have been published and it seemed worthwhile to compile the studies of 2009, 2008 and the second part of 2007. Such an overview covering the scientific literature mainly from 2000 onwards, up to the first half of the year 2007, has been published recently. The focus of this overview lies on the anti‐nociceptive, anticancer, anti‐inflammatory, penetration‐enhancing, insect repellent, antiviral and antioxidative properties of essential oils. Many essential oils have been used for centuries in folk medicine and in recent years the biological properties of various essential oils have been proved by a number of studies. Their use in the treatment of pain, inflammation, viral diseases and cancer and their potential to enhance the penetration of other drugs, their insect repellent activity and their antioxidative effects were confirmed. Nonetheless, more studies are necessary to analyse the biological properties of other essential oils or to prove their mechanism of action. Copyright © 2010 John Wiley & Sons, Ltd.